Recent Developments in Systems Biology and Metabolic Engineering of Plant–Microbe Interactions - Kumar, Vishal; Baweja, Mehak; Singh, Puneet K.; Shukla, Pratyoosh (Frontiers in Plant Science, 2016)
Microorganisms play a crucial role in the sustainability of the various ecosystems. The characterization of various interactions between microorganisms and other biotic factors is a necessary footstep to understand the association and functions of microbial communities. Among the different microbial interactions in an ecosystem, plant-microbe interaction plays an important role to balance the ecosystem. The present review explores plant microbe interactions using gene editing and system biology tools towards the comprehension in improvement of plant traits. Further, system biology tools like FBA, OptKnock and constrain based modeling helps in understanding such interactions as a whole. In addition, various gene editing tools have been summarized and a strategy has been hypothesized for the development of disease free plants. Furthermore, we have tried to summarize the predictions through data retrieved from various types of sources such as high throughput sequencing data (e.g. single nucleotide polymorphism (SNP) detection, RNA-seq, proteomics) and metabolic models have been reconstructed from such sequences for species communities. It is well known fact that systems biology approaches and modeling of biological networks will enable us to learn the insight of such network and will also help further in understanding these interactions.